Exosomes in Cancer Radioresistance - Ni, Jie; Bucci, Joseph; Malouf, David; Knox, Matthew; Graham, Peter; Li, Yong (Frontiers in Oncology, 2019)
Radiation is a mainstay of cancer therapy. Radioresistance is a significant challenge in the treatment of locally advanced, recurrent and metastatic cancers. The mechanisms of radioresistance are complicated and still not completely understood. Exosomes are 40-150 nm vesicles released by cancer cells that contain pathogenic components, such as proteins, mRNAs, DNA fragments, non-coding RNAs and lipids. Exosomes play a critical role in cancer progression, including cell-cell communication, tumour-stromal interactions, activation of signaling pathways and immunomodulation. Emerging data indicate that radiation-derived exosomes increase tumour burden, decrease survival, cause radiation-induced bystander effects and promote radioresistance. In addition, radiation can change the contents of exosomes, which allows exosomes to be used as a prognostic and predictive biomarker to monitor radiation response. Therefore, understanding the roles and mechanisms of exosomes in radiation response may shed light on how exosomes play a role in radioresistance and open a new way in radiotherapy and translational medicine. In this review, we discuss recent advances in radiation-induced exosome changes in components, focus on the roles of exosome in radiation-induced bystander effect in cancer and emphasize the importance of exosomes in cancer progression and radioresistance for developing novel therapy.